2021
DOI: 10.3390/coatings11080937
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Electrical, Structural, Chemical and Optical Properties of PVD Ta(N) Films Deposited with Different N2 Flow Rates

Abstract: By reactive DC magnetron sputtering from a pure Ta target onto silicon substrates, Ta(N) films were prepared with different N2 flow rates of 0, 12, 17, 25, 38, and 58 sccm. The effects of N2 flow rate on the electrical properties, crystal structure, elemental composition, and optical properties of Ta(N) were studied. These properties were characterized by the four-probe method, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and spectroscopic ellipsometry (SE). Results show that the deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…28 the TaN x electrode may evolve gradually from TaN to Ta 3 N 5 as the nitrogen content of TaN x is increased. 29 The broad peak may also correspond to the mixture of TaN (111), Ta 3 N 5 (130), or Ta 3 N 5 (040) due to the mixture of the two-phases (i.e. TaN and Ta 3 N 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…28 the TaN x electrode may evolve gradually from TaN to Ta 3 N 5 as the nitrogen content of TaN x is increased. 29 The broad peak may also correspond to the mixture of TaN (111), Ta 3 N 5 (130), or Ta 3 N 5 (040) due to the mixture of the two-phases (i.e. TaN and Ta 3 N 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that TaN can exhibit resistivity values of 0.3 Ω∙cm at 2 nm thickness [ 26 ] or the 1.5689 × 10 −3 Ω∙cm for a 97.64 nm thick film [ 27 ], it is worth noting that a Cu/TaN system is bound to exhibit higher resistivity values at similar thicknesses. In this way, while this Cu/Ta system displayed lower values than the Cu/Co-W alternative, a conventional dual-layer system comprised of a Ta adhesion layer with a TaN barrier layer should yield a higher sheet resistivity than that observed for the Co-W system at equivalent thickness due to the aforementioned TaN electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The material properties of ionized PVD (IPVD) deposited Ta and TaN are discussed in Hecker and colleagues. [12,14] It has been shown that Ta well meets the requirements for the application as a Cu diffusion barrier. Intermetallic Cu-Ta compounds are nonexistent, [15,16] and the solubility of tantalum in copper is very small.…”
Section: Introductionmentioning
confidence: 99%